2023
DOI: 10.1007/s10639-023-11839-w
|View full text |Cite
|
Sign up to set email alerts
|

Student teachers’ perceptions of flipped classroom in EFL teacher education

Abstract: This paper aims to provide evidence on student teachers’ perceptions of Flipped Classroom (FC) to help teacher educators (TEs) to make informed decisions about implementing FC and support student teachers to reflect on the value of FC in their teaching practice. FC, a pedagogical model requiring digital competence of students and teachers, has been a popular teaching approach for nearly two decades in K-12 and higher education. After the outbreak of Covid-19, more teachers have started to implement FC. In post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, the study also identified several challenges and areas for improvement in implementing PjBL in online courses. The issues related to time management, communication barriers, and technical difficulties underscore the importance of providing adequate support and resources to facilitate seamless collaboration and learning experiences in virtual environments (Han et al, 2024;Muloiwa-klenam & Sharpley, 2023;Preez & Marx, 2023). Additionally, the need for more precise guidelines and instructions reflects the importance of instructor facilitation and scaffolding to optimize the PjBL experience for online learners.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…However, the study also identified several challenges and areas for improvement in implementing PjBL in online courses. The issues related to time management, communication barriers, and technical difficulties underscore the importance of providing adequate support and resources to facilitate seamless collaboration and learning experiences in virtual environments (Han et al, 2024;Muloiwa-klenam & Sharpley, 2023;Preez & Marx, 2023). Additionally, the need for more precise guidelines and instructions reflects the importance of instructor facilitation and scaffolding to optimize the PjBL experience for online learners.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…There is a call for additional research into the implementation of the flipped classroom, paying attention to contextual and subject-specific factors to gain a deeper understanding of both the benefits and challenges associated with this instructional model. Han et al (2024) suggest that future studies should address various subject disciplines, including participants from several teacher education programs, and examine the long-term effects of implementing flipped classrooms.…”
Section: / 12mentioning
confidence: 99%
“…In a recent study, Han et al (2024) investigated how pre-service teachers perceive the flipped classroom. They collected data through surveys and focus group interviews with pre-service teachers specializing in English as a foreign language in Norway.…”
Section: Flipped Classroom In Initial Teacher Educationmentioning
confidence: 99%